1981
DOI: 10.1007/bf00596171
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-frequency electrical stimulation on fast and slow muscles of the rat

Abstract: Leg muscles of adult rats were stimulated chronically at a low-frequency, and the histochemical reactions of various enzymes (succinic dehydrogenase, mitochondrial alpha-glycerophosphate dehydrogenase, phosphorylase, alkali-ATPase and acid-ATPase), capillary density, resistance to fatigue, and contractile properties were studied. Following stimulation, the histochemical properties of muscle fibres in the fast extensor digitorum longus (EDL) and tibialis anterior (TA) muscles became similar to those of the majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
2

Year Published

1984
1984
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 27 publications
1
13
0
2
Order By: Relevance
“…Others found in the musculus extensor digitorum longus and musculus tibialis anterior, fast-twitch muscles of the limb, a change of type 2B into type 2A fibres, the last being intermediate fast-twitch fibres with a fast oxidative glycolytic activity which are better adapted to sustain contraction [30]. However, no increase in slow-type fibres were found in fast limb muscles of the rat [31][32][33] or of the rabbit [20] even after a long stimulation period. Pette and Vrbova [30] suggested that stimulation-induced changes in the muscle fibre population may proceed in the following order: type 2B-type 2D-type 2A-type 2C-type 1C-type 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others found in the musculus extensor digitorum longus and musculus tibialis anterior, fast-twitch muscles of the limb, a change of type 2B into type 2A fibres, the last being intermediate fast-twitch fibres with a fast oxidative glycolytic activity which are better adapted to sustain contraction [30]. However, no increase in slow-type fibres were found in fast limb muscles of the rat [31][32][33] or of the rabbit [20] even after a long stimulation period. Pette and Vrbova [30] suggested that stimulation-induced changes in the muscle fibre population may proceed in the following order: type 2B-type 2D-type 2A-type 2C-type 1C-type 1.…”
Section: Discussionmentioning
confidence: 99%
“…Kwong and Vrbova [31], when stimulating fast-twitch muscles of the rat with 10 Hz during 8, 10 and 24 h a day for 12 to 41 days, saw a higher capillary density and a more homogenous acid-ATPase staining. The unstimulated muscles displayed different degrees of staining intensity (light, intermediate dark).…”
Section: Discussionmentioning
confidence: 99%
“…In animal experimental muscle models for skeletal muscle hypertrophy, NMES is generally performed with intermittent and high frequencies (more than 60 Hz) [1619]. On the other hand, when NMES was applied with a lower electrical frequency (~20 Hz) and long activation times, it led to higher oxidative properties and a fast-to-slow conversion of the muscle fiber phenotype [20]. Therefore, animal experimental models with NMES were used to mimic resistance training and/or endurance exercise in order to test the effects of changes in frequency and stimulation time on muscle hypertrophy [21].…”
Section: Introductionmentioning
confidence: 99%
“…Die tetanic tension (tetanische Spannung) nahm bei intermittierender Stimulation ab der 2. Woche um 12 -13 % zu, die twitch:tetanus ratio stieg an [53,79,96,97,[117][118][119]127,[171][172][173][174][175][176][177]. Auch hier gab es in den ersten beiden Wochen nach Stimulationsbeginn einen vorübergehenden gegenteiligen Effekt [209].…”
unclassified